2013
DOI: 10.1103/physrevlett.111.231801
|View full text |Cite
|
Sign up to set email alerts
|

Possible Resonance Effect of Axionic Dark Matter in Josephson Junctions

Abstract: We provide theoretical arguments that dark-matter axions from the galactic halo that pass through Earth may generate a small observable signal in resonant S/N/S Josephson junctions. The corresponding interaction process is based on the uniqueness of the gauge-invariant axion Josephson phase angle modulo 2π and is predicted to produce a small Shapiro steplike feature without externally applied microwave radiation when the Josephson frequency resonates with the axion mass. A resonance signal of so far unknown or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
81
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 45 publications
14
81
1
1
Order By: Relevance
“…Interestingly enough, this range of the axion mass m a 10 −4 eV is perfectly consistent with recent claim [39], [40] that the previously observed small signal in resonant S/N/S Josephson junction [41] is a result of the dark matter axions with the mass m a 1.1 · 10 −4 eV. We conclude this section on optimistic note with a remark that the most interesting region of the parametric space with mean baryon charge B…”
Section: Implications For the Axion Search Experimentssupporting
confidence: 92%
“…Interestingly enough, this range of the axion mass m a 10 −4 eV is perfectly consistent with recent claim [39], [40] that the previously observed small signal in resonant S/N/S Josephson junction [41] is a result of the dark matter axions with the mass m a 1.1 · 10 −4 eV. We conclude this section on optimistic note with a remark that the most interesting region of the parametric space with mean baryon charge B…”
Section: Implications For the Axion Search Experimentssupporting
confidence: 92%
“…The result in equation (28) and that given by Beck [54] both satisfy the constraint put by Hoskins et al [55], who found that the local density of non-virialized axionic dark matter should not exceeds 0.2 GeV/cm 3 . According to the BEC theory, the critical temperature is given as [56] T c = 2π…”
Section: Mass Density and Critical Temperaturesupporting
confidence: 77%
“…So, there is a need for solutions that can lead to an increase in the axion detecting mode volume while preserving the number of detecting systems and high resonant frequency. In particular, high mass axions yielding high frequency photons (> 15GHz) are motivated theoretically [13], and by some curious experimental results [14], but are as yet largely unprobed, although some recent proposals and experiments have begun to move in this direction [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%